PROJECT-BASED LEARNING USING DIGITAL COMICS TO IMPROVE WRITING SKILL OF EXPERIMENTAL REPORT TEXT - Cahyo Hasanudin; Ayu Fitrianingsih; Joko Setiyono; Nofia Fitriyana (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
Writing experimental report text is a compulsory material for Indonesian language subject in ninth grade of junior high school. This study aims to 1) find out the implementation of project-based learning using digital comics, and 2) find out the improvement of students’ writing in experimental report text in the project-based learning using digital comics. This study is a classroom action research with the subjects of ninth grade students totaling 50 males. This study uses a test question instrument. Data were collected using the test method and the data were validated by triangulation technique. The data analysis technique used is a comparative descriptive technique and a critical analysis technique. The conclusions of this study are 1) in implementing project-based learning assisted by digital comics, researchers apply learning syntax starting from (1) pre-project, (2) phases, and (3) post-project, and 2) the improvement of students' writing skill of experimental report texts in ninth grade classically starts from pre-action as much as 32%, cycle I as much as 58%, and cycle II as much as 88%.